(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
The province of Cabo Delgado, in the extreme north of Mozambique, is experiencing a difficult situation of armed conflict linked to the presence of an “Islamist” insurgency launched by the group known as al-Shabaab. The essay reconstructs and analyses the main topics and the most relevant axes of this complex political and social process, by examining in particular: origins and characteristics of the group, the ways in which it was formed, the main reasons underlying the phenomenon, placing them within the socio-economic context of the region. Finally, it discusses some aspects related to military responses to the rebellion, including the role of some international actors.